Dental modification practices on the Cape Flats in the Western Cape - Friedling, Louise J (Department of Human Biology, 2017)
The people living on the Cape Flats in the Western Cape have been practicing dental modification for a number of years. A systematic survey of eight adjoining areas in the Northern suburbs was done to investigate the prevalence, motivation and possible historical time depth of this practice. The survey was conducted by means of a questionnaire. A total of 2167 individuals participated in this study of which 41 % had modified their teeth. More males (44.8%) than females (37.9%) were involved in this practice. Residential area and pay class had an impact on dental modification practices as the incidence increased within lower income areas. Six styles of modification were identified, of these; the removal of the upper four incisors (style 400) was often the style of choice (93. 7%). There were four stated reasons (peer pressure, fashion, gangsterism and medical/other) for dental modification of which peer pressure (in males) and fashion (in females) were the most popular. Dentists did most of the extractions. Three quarters of the entire study sample had family members with dental modifications. More than half (69.8%) of individuals with modifications wore dentures. Not only coloured people were modifying their teeth, some study subjects who had self-classified themselves as black or white also practiced it.